Tingkat Keganasan Saprolegnia parasitica Pada Ikan Patin (Pangasius hypophthalmus Sauvage) dan Tindakan Kuratif Alaminya dengan Lactobacillus plantarum - Atira Atira (Biocelebes, 2011)
Research of S. parasitica parasitic on cathfish that would inhibit mycelium growth with L. plantarum conducted according to in vivo and in vitro. This research conducted to find out infection concentration of S. parasitica on catfish, and research L. plantarum concentration that inhibit or cure parasitic disease of S. parasitica on cathfish. This research consist of two steps, first step that is concentration of zoospore suspension count that cause 50% infection on catfish. Secondly step that is ability test concentration variation of L. plantarum within inhibit parasite on cathfish. First research step conducted according to experimental laboratory, that is REED-MUENCH method was used to determine IC50. Observed parameter was number of infected catfish by S. parasitica, and its infection diameter. Second step that is curative test was conducted from infected catfish by S. parasitica with L. plantarum inoculums. Used design was Completely Randomized Design with factorial pattern that was 4 x 4, with first factor consisted of 4 infection concentration of S. parasitica suspension, i.e. 0xIC50, IC50 (Infectious Concentration 50%), 2xIC50, and 4xIC50. Second factor was consisted of 4 concentration of L. plantarum FNCC 226 inoculums, i.e. MaxNLC (Maximal Nir Lethal Concentration), ½xMaxNLC, ¼xMaxNLC, dan 0xMaxNLC, with 4 times replication. Observed parameter was comparison of infection diameter of S. parasitica on catfish before and after curative concentration giving of L. plantarum inoculums. First step research result about IC50 count showed that infection concentration for 50% was are 1 x 107 zoospore/mL. Increment of zoospore concentration was along with increment of infection diameter on cathfish. Second step research result about curative, that L. plantarum 7,7 x 105 cfu/mL (MaxNLC), 4,0 x 105 cfu/mL (½xMaxNLC), 2,3 x 105 cfu/mL (¼xMaxNLC) could inhibit mycelium of S. parasitica. Decrement of S. parasitica infection, was along with increment of L. plantarum capacity blocked. Mycelium diameter of S. parasitica decrement very real after giving L. plantarum.